Ensaio experimental e modelagem de arrefecimento passivo de módulos fotovoltaicos flutuantes com pontes de calor em contato com água - Busson, Bruna de Oliveira (2019)
Photovoltaic (PV) modules convert part of solar radiation absorbed by the PV cells into electrical energy, the remainder causes an increase in internal energy of the PV cells and, consequently, an increase in the PV module operating temperature and a reduction in electrical performance. Solutions have been proposed to mitigate these effects and improve PV conversion efficiency. In this context, this work proposes the passive cooling of floating PV module using heat bridges to reduce the module temperature and increase the energy conversion efficiency. The modeling developed for prediction of the floating module operating temperature with heat bridges predicts the cooling capacity of the proposal. The proposed model is nonlinear algebraic and equations require iterative numerical solution performed in spreadsheet. Data obtained experimentally from a 20 Wp polycrystalline floating module without heat bridges in LEA/UFC served to calibrate the model parameters. After defining the parameters, the model has presented satisfactory behavior during the entire PV module electricity production period regardless of daily irradiation level. Data allowed to compare thermal and electrical behavior of a floating PV module with 5 fixed heat bridges and a conventional PV module, both in LEA/UFC, over 5 months. The floating module temperature was below the conventional module temperature by 3.2°C, on average. The model developed for floating module with heat bridges may predict the operating temperature with error around 5% when irradiation was over 5.0 kWh/m². The daily electricity generation of the floating PV module with heat bridges, in turn, presents gains compared to the conventional PV module electricity generation without extra energy costs of 42% for irradiation below 2.5 kWh/m² (minimum irradiation level), 31% for irradiation between 2.5 kWh/m² and 5.0 kWh/m² (medium irradiation level) and 24% for irradiation greater than 5.0 kWh/m² (maximum irradiation level). At the same time, the results showed gains in the conversion efficiency of heat-bridged floating modules compared to conventional modules. Thus, the modeling developed for floating modules with heat bridges could predict the thermal behavior and prove the effect of passive cooling.